Risk factors and microbiological features of surgical site infections - Dr. Atul Kumar; Dr. Shivani Sinha (Tropical Journal of Pathology and Microbiology, 2021)
Background: Surgical site infections are the infections of the tissues, organs or spaces exposed by surgeons during the performance of an invasive procedure manifested in the postoperative period within 30 days after a surgical procedure and up to one year if an implant was placed in the patient. SSI is still higher in India as compared to western data leading to increased morbidity and mortality. This study aimed to analyse the factors associated with SSI and its microflora in a tertiary care centre.Methods: A descriptive cross-sectional study was done for one year in a tertiary care centre in Bareilly, U.P. All the patients who underwent surgeries related to git pathology in the surgery department, either emergency or elective with surgical site infections, were included in this study. Patients less than 18, all cases operated else were, or re-operated were excluded from this study. All traumatic abdominal surgeries were also excluded from this study.Results: The present study revealed SSI was associated with 82 (9.4%) cases among elective and 80 (21%) in emergency surgeries. Superficial incision SSI was found to be most common (90 cases), followed by deep incisional SSI (60 patients) and organ/space SSI (12 cases). Minor intestine surgeries were most commonly associated with SSI. The microbiological organism most widely isolated was E. Coli (41.2%), followed by Staphylococcus aureus (27.5%), Klebsiella (16.5%), group A beta-haemolytic Streptococci (9.1%) and Pseudomonas (5.5%).Conclusions: Surgical site infection still causes considerable morbidity and high cost to the health care system and is becoming increasingly crucial in medico-legal aspects. Prevention of SSI requires a targeted approach to improve health care workers' knowledge, practising the guidelines strictly regarding asepsis and optimising the patient before surgery. Reduction in rate of SSI will improve cosmesis and make the results of operations better as a whole.